2021
DOI: 10.1111/1467-9566.13414
|View full text |Cite
|
Sign up to set email alerts
|

“They created a team of almost entirely the people who work and are like them”: A qualitative study of organisational culture and racialised inequalities among healthcare staff

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 29 publications
3
31
0
Order By: Relevance
“…Microaggressions and tokenism, often more subtle than outright discrimination, reinforce systemic inequality in the workplace (Resnick & Galupo, 2019;Woodhead et al, 2021). Many participants suggested that more diversity within the child life profession would improve their own experience in the workplace and potentially mitigate their experiences of microaggressions, othering, tokenism, and discrimination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microaggressions and tokenism, often more subtle than outright discrimination, reinforce systemic inequality in the workplace (Resnick & Galupo, 2019;Woodhead et al, 2021). Many participants suggested that more diversity within the child life profession would improve their own experience in the workplace and potentially mitigate their experiences of microaggressions, othering, tokenism, and discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…Less has been published about the experiences of child life specialists with marginalized racial, ethnic, sexual orientation, age, and disability identities. The extant literature indicates that while increased workforce diversity may reduce racial and ethnic health disparities (Phillips & Malone, 2014), a significant barrier to this diversity is the discriminatory experiences of health care providers with marginalized identities (Sim et al, 2021;Woodhead et al, 2021). Retention of diverse providers depends on a hospital system's ability to provide a safe environment.…”
mentioning
confidence: 99%
“…The TIDES study aims to understand how discrimination experiences contributes to inequalities in health and health services. Full details of the methods and sample description were previously reported (7,8).…”
Section: Designmentioning
confidence: 99%
“…Ethnic minority staff are also more likely to experience bullying and discrimination from both colleagues and managers (particularly in London Trusts) (7). Such incidents are associated with poor mental and physical health outcomes, which in turn can lead to increased sick leave and negatively impact overall quality of life (7,8). These discriminatory experiences compound the already highly stressful work environment that nursing students are exposed to during their training (11,12), ultimately resulting in high staff attrition among student nurses (11,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation